KEKUATAN BALOK BETON BAJA RINGAN SISTIM TRUSS PADA BALOK KONVENSIONAL DAN PRECAST - A Rudi Hermawan; Suripto; Yanuar; Eka Sasmita Mulya, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Research of concrete beam truss system having two type of beam that was conventional concrete beam truss systerm and connection precast concrete beam trsuss system. And Research of concrete beam truss system having some problems, that was how about performance of concrete beam truss sytem if load was applicated at top of concrete beam at two point. The aim of research was determined of performance of concrete beam if load was applicated at top of concrete bream at two point load. Result of research have different performance between cncrete beam conventional truss system with concrete beam precast connection truss sytem. Concrete beam conventional truss system was achieve a load 228,0 kN and 3,9 mm for deflection. Concrete beam precast connection truss system was achieved a load 191,0 kN and 4,1 mm for deflection. For momen maximum, concrete beam conventional truss system was achieve a momen 41,8 kN-m and 35,0 kN-m for concrete beam precast connection truss system. For flexurer strength, concrete beam conventional truss system was achieve a flexurer strength 11,5 Mpa and 9,6 Mpa for concrete beam precast connection truss system.